Toward standardization, harmonization, and integration of social determinants of health data: A Texas Clinical and Translational Science Award institutions collaboration - Catherine K. Craven; Linda Highfield; Mujeeb Basit; Elmer V. Bernstam; Byeong Yeob Choi; Robert L. Ferrer; Jonathan A. Gelfond; Sandi L. Pruitt; Vaishnavi Kannan; Paula K. Shireman; Heidi Spratt; Kayla J. Torres Morales; et al. (Journal of Clinical and Translational Science, 2024)
Abstract